THE IMAGE OF WOMEN IN THE WOMEN’S MAGAZINES DURING THE DEMOCRAT PARTY PERIOD (1950-1960) - Dilara KOÇER (Zeitschrift für die Welt der Türken, 2009)
The aim of this study is to analyse the representation of women by 17 women’s magazines published in 1950-1960. The major goal of the study is to examine the image of woman in Turkey’s democratisation experience during the DP period. It is argued that the magazines advise women a role model pulling backward them.